The role of collective effects on settling velocity enhancement for inertial particles in turbulence. (11th May 2018) - Huck, P. D.; Bateson, C.; Volk, R.; Cartellier, A.; Bourgoin, M.; Aliseda, A.
Abstract : A particle-laden homogeneous isotropic turbulent flow is studied experimentally to understand the role of collective effects (e.g. particle–particle aerodynamic interactions caused by local particle accumulation) on the settling velocity of inertial particles (Stokes number: $0.3<St<0.6$ ). Conditional averaging of the particle vertical velocity on the local concentration identifies three settling regimes: modest enhancement by single particle–turbulence interactions in low concentration regions, rapid settling velocity increases in clusters at intermediate concentrations and saturation of the settling enhancement at large concentrations. The latter effect, associated with four-way coupling, displays qualitative agreement with simulations in the literature and is a new experimental observation. Fluctuations up to an order of magnitude larger than the background volume fraction are measured using Voronoï analysis. A model is developed following a classic volume-averaged multiphase flow methodology to provide an interpretation of the three settling regimes and quantitative predictions consistent with the measurements.